Platfrom Video Game sebagai Media Terapeutik - Yunike Yunike; Ira Kusumawaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study attempts to use video games therapeutically, which can be used as a rationale for developing and utilizing video games as a therapeutic medium. This research method uses the PRISMA approach using the keywords